Disentangling the Role of Contract Types and Sector Disparities for Public Service Motivation - Grund, Christian; Thommes, Kirsten
The intention of "doing good for society" is regarded to be a crucial motivator for employees in the public sector in order for them to perform well. Recent research in the public sector literature calls for a deeper understanding of how this specific public service motivation (PSM) is shaped. In our paper, we analyze how different degrees of inclusion in the public sector impact PSM. We also investigate how prospects of employment relations (fixed-term versus permanent contracts), temporal differences (part-time versus full-time employment), and actual jobs (core versus subsidiary jobs) moderate PSM in public service. Our findings show that aspects of PSM are affected by these employment characteristics in various ways, suggesting that the factors influencing PSM are multifaceted and that actual employment conditions have to be taken into consideration when assessing PSM.

Cooperation in Diverse Teams: The Role of Temporary Group Membership - Grund, Christian; Harbring, Christine; Thommes, Kirsten
In organizations, some team members are assigned to a team for a predefined short period of time, e.g., as they have a temporary contract, while others are permanent members of the same team. In a laboratory experiment we analyze the cooperation levels resulting from diverse teams, where some team members remain with a team and others are switching teams. Our results reveal that teams consisting partly of members with temporary membership display a lower productivity compared to teams of permanent team members only. First, temporary team members cooperate less than permanent team members. Second, individual effort decisions increase with the number of team mates who are of the same type. This second effect holds for both temps and permanents. We argue that social identity is affected by team composition and the individuals' role in a team.

Künstliche Intelligenz in der industriellen Arbeitswelt - Papenkordt, Jörg; Gabriel, Stefan; Thommes, Kirsten; Dumitrescu, Roman
Im Rahmen dieser Studie wird der Status Quo des KI-Einsatzes in der industriellen Arbeitswelt in der Region OstWestfalenLippe erfasst und beschrieben. Dadurch wird eine Grundlage geschaffen, um eine zielführende Unterstützung der Gestaltung von durch Künstliche Intelligenz (KI) gestützter Arbeitsprozesse in Unternehmen zu ermöglichen, indem beispielsweise bedarfsbezogene Maßnahmen entwickelt und durchgeführt sowie weiterer Forschungsbedarf aufgezeigt wird. Die Befragung wurde im Jahr 2021 von dem Kompetenzzentrum Arbeitswelt.Plus sowie dem Spitzencluster it’s OWL initiiert. Dabei sind drei Zielgruppen – Unternehmensleitung, Personalabteilung (HR) sowie Arbeitnehmer*innen – adressiert worden. Insgesamt nahmen 317 Personen aus 89 verschiedenen Unternehmen bzw. Organisationen an der Befragung teil – zu 38 % Unternehmer*innen, zu 13 % Personaler*innen und zu 49 % Arbeitnehmer*innen. Die meisten der Teilnehmenden stammten aus der Elektroindustrie, dem Maschinenbau sowie dem Informations- und Kommunikationstechnologie (IKT)-Sektor. Die Befragungsergebnisse zeigen, dass sich die meisten Unternehmen in der Anfangsphase der KI-Nutzung befinden. Zwischen einzelnen Unternehmensbereichen und verschiedenen Branchen zeigen sich gewisse Unterschiede in der Nutzungsphase. Die Befragten stehen aktuell vor der Nutzung von vor allem teilautonomen KI-Systemen, die ausführende und analytische menschliche Tätigkeitenbeispielsweise durch Informationsbereitstellungen unterstützen. Wesentliche Ziele der KI-Nutzung sind die Effizienzsteigerung, Qualitätsverbesserung, Entscheidungsoptimierung sowie Unterstützung der Arbeitnehmer*innen. Allerdings werden in allen Unternehmen die fehlende Expertise sowie insgesamt die Komplexität des Themenfelds als Hinderungsgründe identifiziert. In allen Unternehmen und allen Unternehmensbereichen werden hohe Auswirkungen durch KI erwartet. Auf die Arbeitsgestaltung werden insgesamt eher positive Auswirkungen erwartet. Die Befragten schätzen die Bedeutung von KI, ihre Aufgeschlossenheit sowie ihr Vertrauen gegenüber KI als insgesamt hoch ein, ihr Verständnis von KI dagegen eher als gering. Tendenziell zeigt sich eine große Diskrepanz zwischen Selbst- und Fremdbild mit einer teils deutlich negativeren Wahrnehmung anderer. Die Befragten erwarten außerdem steigende Kompetenzanforderungen sowie einen hohen Weiterbildungsbedarf, insbesondere bezüglich des grundlegenden Verständnisses über KI. In den wenigsten Unternehmen existiert jedoch ein gezieltes Weiterbildungsangebot. Die Erkenntnisse aus der Befragung fließen im Rahmen des Kompetenzzentrums Arbeitswelt.Plus in die gezielte Gestaltung und Einführung KI-gestützter Arbeitsformen sowie bedarfsgerechter Unterstützungsangebote ein. Die hohe Komplexität der KI-Einführung sowie die sowohl technischen als auch mitarbeiterbezogenen Herausforderungen verdeutlichen den Bedarf für eine soziotechnische Perspektive und ein systematisches Vorgehen bei der Gestaltung dieses vielschichtigen Themenfelds.

Care robots in society: Knowledge and orientation needs - Pekkarinen, Satu; Hennala, Lea; Tuisku, Outi; Gustafsson, Christine; Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Melkas, Helinä (Gerontechnology)

The need for care robot orientation in elder care services - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helinä; Gustafsson, Christine (Gerontechnology)

Age and tenure diversity on the work floor: Evidence from a natural field experiment in production - Thommes, Kirsten; Klabuhn, Janny (Evidence-based HRM)

Care Robot Orientation: What, Who and How? Potential Users` Perceptions - Johansson-Pajala, Rose-Marie; Thommes, Kirsten; Hoppe, Julia Amelie; Tuisku, Outi; Hennala, Lea; Pekkarinen, Satu; Melkas, Helina; Gustafsson, Christine (International Journal of Social Robotics)

Can digital feedback increase employee performance and energy efficiency in firms? Evidence from a field experiment - Hoffmann, Christin; Thommes, Kirsten (Journal of Economic Behavior & Organization)

Decisions on Extending Group Membership—Evidence from a Public Good Experiment - Grund, Christian; Harbring, Christine; Thommes, Kirsten; Tilkes, Katja Rebecca (Games)
We experimentally compare the consequences for group cooperation of two decision mechanisms involving the extension of group membership. We analyze an exogenous decision (random draw) and an endogenous decision (made by a particular group member) mechanism to extend a temporary agent’s group membership. Our results reveal that the prospect of group membership extension affects not only the temporary but also the permanent group members’ contributions with an endogenous mechanism.

Group (Re-) formation in public good games: The tale of the bad apple? - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Journal of Economic Behavior & Organization)

The Role of Contract Types for Employees’ Public Service Motivation - Grund, Christian; Thommes, Kirsten (Schmalenbach Business Review)

Peer influence on protest participation: Communication and trust between co-workers as inhibitors or facilitators of mobilization - Born, Marieke; Akkerman, Agnes; Thommes, Kirsten (Social science research)

Public good provision in blended groups of partners and strangers - Grund, Christian; Harbring, Christine; Thommes, Kirsten (Economics Letters)

Behavioral spillovers from freeriding in multilevel interactions - Thommes, Kirsten; Vyrastekova, Jana; Akkerman, Agnes (Journal of Behavioral and Experimental Economics)

The internal market and the consumer: what consumers actually choose - Thommes, Kirsten; Faure, Michael; Heine, Klaus (Colum. J. Eur. L.)

The dark side of solidarity: social norms and social relations in the aftermath of strikes - Thommes, Kirsten; Akkerman, Agnes; Torenvlied, René; Born, Marieke (Industrial relations journal)

HRM and the use of personnel services: an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Weiland, Katrin; Thommes, Kirsten (International journal of manpower)

HR outsourcing and service quality: theoretical framework and empirical evidence - Braun, Irene; Pull, Kerstin; Alewell, Dorothea; Störmer, Susi; Thommes, Kirsten (Personnel Review)

Explanatory factors for firms’ use of temporary agency work in Germany - Thommes, Kirsten; Weiland, Katrin (European Management Journal)

Triggers of HR outsourcing decisions--an empirical analysis of German firms - Alewell, Dorothea; Hauff, Sven; Thommes, Kirsten; Weiland, Katrin (The International Journal of Human Resource Management)